Recreational drug use as everyday life: explorations of young adults' gendered motivations for taking drugs in Nigeria - Dumbili, Emeka W. (Routledge handbook of intoxicants and intoxication, 2023)
The use of psychoactive substances for recreational and therapeutic purposes is increasing in Nigeria. Yet, there is a shortage of studies investigating the motivations for using drugs in the country. Drawing on gender theories, this chapter reports on data elicited through semi-structured interviews with young adults (aged 23–29 years) who use drugs for diverse reasons in South-Eastern Nigeria. Interviewees reported extensive personal experience taking cannabis, tramadol, Rohypnol, codeine, and methamphetamine, and discussed how coping and enhancement motives influence drug use. Although taking multiple substances was common among them, instrumental drug use was widespread among cannabis and tramadol users. For example, men used tramadol mainly to boost sexual prowess, prolong sexual intercourse, and maintain masculine ego because they believe that women prefer sexual partners who last longer than the natural limit. Women used drugs to activate sexual feelings and prepare for sex. Interviewees also used intoxicants to attenuate anger, sorrow, and depression, but only women reported using drugs to ameliorate emotional turmoil due to relationship problems. Findings also show that the performance of masculinities motivated drug use; thus, men reproduced traditional masculinity by engaging in ‘cannabis smoking games/competitions’. Relatedly, women engaged in the constructions of counter-normative intoxication practices by introducing men to drugs and by smoking cannabis with them. The desire to boost and maintain masculine ego by satisfying women who mock men for not lasting beyond the natural period during sex facilitated drug use according to men. The findings highlighted critical risks associated with drug use and how these risks are normalized within social groups.